Pengaruh Media Perebusan Terhadap Komposisi Mineral Kerang Air Tawar Meti (Batissa violacea Lamarck, 1818): Boiling Media Effect on Mineral Composition of Meti Fresh Water Mussels (Batissa violacea Lamarck, 1818) - Handayani, Kiki Rizki; Yuyun, Yonelian; Jamaluddin (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
This research aims were to analyzed mineral composition of fresh and processed meti freshwater mussels (Batissa violacea Lamarck,1818) and to know the effect of boiling media on the mineral composition with various added boiling media conditions that are water, NaCl 1%, and acetic acid 0.5%. Mineral compositions were tested with microwave digestion and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) method. Mineral composition of fresh mussel were consisted of calcium (Ca) 10412 mg/kg, cobalt (Co) 0,182 mg/kg, copper (Cu) 3,54 mg/kg, magnesium (Mg) 345 mg/kg, mangan (Mn) 13,6 mg/kg, phosphor (P) 7753 mg/kg, potassium (K) 1163 mg/kg, sodium (Na) 291 mg/kg, and zinc (Zn) 44,2 mg/kg. The results of research on freshwater mussels in boiling media of water, NaCl 1%, and acetic acid 0.5% gave effect on the levels of minerals of calcium (Ca), magnesium (Mg), phosphor (P), potassium (K), sodium (Na ), cobalt (Co), copper (Cu), mangan (Mn) and there is no effect on the levels of zinc (Zn).